Prenatal cerebellar growth is altered in congenital diaphragmatic hernia on ultrasound. (10th July 2021) - Van der Veeken, Lennart; Russo, Francesca M.; Litwinska, Ewelina; Gomez, Olga; Emam, Doaa; Lewi, Liesbeth; Basurto, David; Van der Veeken, Stephan; De Catte, Luc; Gratacos, Eduard; Eixarch, Elisenda; Nicolaides, Kypros; et al.
Abstract: Objective: Children with congenital diaphragmatic hernia (CDH) are at risk for neurodevelopmental delay. Herein we report on prenatal changes in biometry and brain perfusion in fetuses with isolated CDH. Study Design: This retrospective study evaluated fetuses with isolated, left‐sided CDH in three European referral centers. Abdominal circumference (AC), femur length (FL), head circumference (HC), transcerebellar diameter (TCD), middle cerebral artery (MCA) Doppler, and ventricular width (VW) were assessed during four gestational periods (<24 weeks, 25–28 weeks, 29–32 weeks, >33 weeks). Z‐scores were calculated, and growth curves were created based on longitudinal data. Results: In 367 fetuses, HC, AC and FL were within normal ranges throughout gestation. The TCD diminished with advancing gestational age to fall below the fifth percentile after 32 weeks. A less pronounced but similar trend was seen in VW. The peak systolic velocity of the MCA was consistently approximately 10% lower than normal. Disease severity was correlated to TCD ( p = 0.002) and MCA doppler values ( p = 0.002). There were no differences between fetuses treated with FETO and those managed expectantly. Conclusion: Fetuses with isolated left‐sided CDH have a small cerebellum and reduced MCA peak systolic velocity. Follow up studies are necessary to determine the impact of these changes on neurodevelopment. Key points: What's already known about this topic? Children with congenital diaphragmatic hernia (CDH) are at increased risk for neurodevelopmental problems. It remains uncertain if brain development is already impaired prenatally What does this study add? Fetuses with isolated CDH have a smaller than average cerebellum but normal sized head, which may indicate an altered prenatal brain development in CDH This study is the first to report on biometry and cerebellar and ventricular growth curves and brain blood flow in fetuses with CDH